2016
DOI: 10.1155/2016/7678486
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Anticancer Activity of New Benzofuran Substituted Chalcones

Abstract: Benzofuran derivatives are of great interest in medicinal chemistry and have drawn considerable attention due to their diverse pharmacological profiles including anticancer activity. Similarly, chalcones, which are common substructures of numerous natural products belonging to the flavonoid class, feature strong anticancer properties. A novel series of chalcones, 3-aryl-1-(5-bromo-1-benzofuran-2-yl)-2-propanones propenones (3a–f), were designed, synthesized, and characterized.In vitroantitumor activities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
(44 reference statements)
0
18
0
1
Order By: Relevance
“…61 I No. 4 to the targeted nucleophiles/sites with appropriate selectivity. 3,4 It is widely known that benzo [b]furan derivatives substituted at C-2 (2 nd numbered carbon of five membered rings in benzofuran) position show cytostatic and/or cytotoxic activity.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…61 I No. 4 to the targeted nucleophiles/sites with appropriate selectivity. 3,4 It is widely known that benzo [b]furan derivatives substituted at C-2 (2 nd numbered carbon of five membered rings in benzofuran) position show cytostatic and/or cytotoxic activity.…”
Section: Original Articlementioning
confidence: 99%
“…4 to the targeted nucleophiles/sites with appropriate selectivity. 3,4 It is widely known that benzo [b]furan derivatives substituted at C-2 (2 nd numbered carbon of five membered rings in benzofuran) position show cytostatic and/or cytotoxic activity. 5 On scrutinizing the current research on tetrahydrobenzofurans, we can keep a record of the significant work carried out on it and can make a huge list on benzofuran derivatives (for example, ailanthoidol, a neolignan derivative) which makes it a "spectacular" in cancer therapy.…”
Section: Original Articlementioning
confidence: 99%
“…We considered the anticancer properties of the 2-arylbenzofurans [ 8 , 11 , 12 ] and their photophysical properties as potential photosensitizing anticancer agents [ 11 ] and decided to link the two pharmacophores in order to comprise benzofuran-chalcone hybrids. The most common framework of benzofuran-chalcone hybrids, that we encountered in the literature, have the α,β-unsaturated carbonyl moiety attached to the C-2 or C-3 position of the heterocyclic ring–either through the carbonyl [ 13 , 14 , 15 ] or through the β-carbon [ 16 ]. Very few examples of the benzo[ b ]furan-chalcone hybrids, in which an α,β-unsaturated moiety is appended to the fused benzo ring, existed in the literature [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, as an anticancer agent it is necessary to find drugs with minimum adverse effects those provide more hope for patients. Hence, the use of chalcone derivatives was considered for minimizing unwanted side effects [22,23,24,25]. In addition, several studies revealed the ability of chalcone derivatives to become an important antimicrobial, antifungal, anti-mycobacterial, antimalarial, antiviral, anti-inflammatory, antioxidant, antileishmanial anti-tumor, and anticancer agents [26,27,28].…”
Section: Introductionmentioning
confidence: 99%